Germ-free housing conditions do not affect aortic root and aortic arch lesion size of late atherosclerotic low-density lipoprotein receptor-deficient mice. (1st November 2020) - Kiouptsi, Klytaimnistra; Pontarollo, Giulia; Todorov, Hristo; Braun, Johannes; Jäckel, Sven; Koeck, Thomas; Bayer, Franziska; Karwot, Cornelia; Karpi, Angelica; Gerber, Susanne; Jansen, Yvonne; Wild, Philipp; et al.
ABSTRACT: The microbiota has been linked to the development of atherosclerosis, but the functional impact of these resident bacteria on the lesion size and cellular composition of atherosclerotic plaques in the aorta has never been experimentally addressed with the germ-free low-density lipoprotein receptor-deficient ( Ldlr −/- ) mouse atherosclerosis model. Here, we report that 16 weeks of high-fat diet (HFD) feeding of hypercholesterolemic Ldlr −/- mice at germ-free (GF) housing conditions did not impact relative aortic root plaque size, macrophage content, and necrotic core area. Likewise, we did not find changes in the relative aortic arch lesion size. However, late atherosclerotic GF Ldlr −/- mice had altered inflammatory plasma protein markers and reduced smooth muscle cell content in their atherosclerotic root plaques relative to CONV-R Ldlr −/- mice. Neither absolute nor relative aortic root or aortic arch plaque size correlated with age. Our analyses on GF Ldlr −/- mice did not reveal a significant contribution of the microbiota in late aortic atherosclerosis.